Pemberdayaan Keluarga dalam Mencegah Luka Kaki Diabetes pada Masyarakat di Dusun IV Desa Bangun Rejo Kecamatan Tanjung Morawa Tahun 2024 - Petra Diansari Zega; Ali Imran Sirait; Pretty Egina Sembiring; Anita Sinaga; Verti Angelia Sihombing (Lembaga Pengembangan Kinerja Dosen, 2024)
Diabetes mellitus is a chronic heterogeneous metabolic disorder with complex pathogenesis. It is characterized by elevated blood glucose levels or hyperglycemia, which results from abnormalities in either insulin secretion or insulin action or both. Prevention of diabetic foot ulcers is to empower families to take care for family members with diabetes. The results of the pre-test obtained showed that family knowledge was in the good category of 55.6%. After education was carried out on the role of families in caring for diabetic patients, especially preventing diabetic foot ulcers, the results showed that there was an increase in family knowledge of 70.4%. Families empowered to carry out their roles by helping families with diabetes to meet their diet, motivating them to do physical activity and supporting them to carry out routine health checks. The conclusion of this community service activity is that family empowerment is very useful for preventing diabetic foot ulcers.